Easification of science texts and reading comprehension among high school students - Manaay, Dexter Suganob (2007)
The study used the easification devices introduced by Bhatia (1983) on the biology text of second year high school students. The subjects were from two intact classes handled by the researcher as an English subject teacher. The test results showed that despite the incomparability of the 2 groups in terms of mental abilities, several mean scores showed no significant differences between them. Likewise, qualitative data analyses gathered from the essay responses and interview revealed a favorable result. Reading teachers would do well to teach the easification technique to students to enable them to better comprehend texts across subject areas in school. Easification would develop students' analytical skills, resulting in greater understanding of the subject matter.
Thesis (M.A. Language Education)--University of the Philippines Diliman.
Keywords: Reading (Secondary) -- Philippines -- Makati City; Science -- Study and teaching (Secondary) -- Philippines -- Makati City; Reading comprehension -- Philippines -- Makati City